Microcapsule-coated phosphorus-based flame retardant, and preparation method and application thereof

CN123003984APending Publication Date: 2026-10-30GUANGDONG TAISU NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611380581.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]尽管如此,现有微胶囊包覆型磷系阻燃剂仍存在一些明显的应用问题,例如壳层材料局限性大,导致其致密度不足以及与聚酰胺、聚酯等工程塑料基体界面结合力较弱,且在应用过程中可能因为高温或剪切作用出现包覆层破裂现象,导致PH3抑制不彻底,仍对高端电子电器金属部件构成腐蚀风险,以及后续的析出现象消除不彻底

Benefits of technology

1、本申请制备的微胶囊包覆型磷系阻燃剂,通过壳层结构的原料配方,有效解决了传统包覆层致密度不足及加工剪切易破裂的问题,使阻燃剂在高温加工和长期服役过程中保持包覆完整性,显著抑制磷化氢的释放风险,降低对金属部件的腐蚀隐患,另一方面加强了其与聚合物基体之间的界面结合性,大幅改善了两者间的界面相容性,有效避免了阻燃剂在制品使用过程中的迁移析出,保证了材料长期阻燃性能的稳定性与外观持久性,尤其适用于对可靠性和安全性要求严苛的工程塑料和电子电器部件材料领域中的应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the field of flame retardants, in particular to a microcapsule coated phosphorus-based flame retardant and a preparation method thereof.A microcapsule coated phosphorus-based flame retardant, a raw material scheme of which comprises red phosphorus powder, shell layer combined materials, shell layer additives, dispersants, wetting agents, initiators, dispersion stabilizers, composite functional agents and deionized water and the like.The microcapsule coated phosphorus-based flame retardant prepared by the application can significantly inhibit the release risk of phosphine, reduce the corrosion hidden danger of metal parts, and further strengthen the interface bonding between the flame retardant and a polymer matrix, greatly improve the interface compatibility between the flame retardant and the polymer matrix, effectively avoid the migration and precipitation of the flame retardant during the use of products, and is especially suitable for application in the fields of engineering plastics and electronic and electrical component materials which have strict requirements on reliability and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of cleaning agents, and in particular to a microencapsulated phosphorus-based flame retardant, its preparation method, and its application. Background Technology

[0002] With the widespread use of engineering plastics such as polyamides and polyesters in electronics, new energy vehicles, and communication equipment, flame retardancy and safety have become core performance indicators. Phosphorus-based flame retardants, due to their advantages such as high flame retardancy efficiency, low smoke density, and halogen-free environmental friendliness, are gradually replacing traditional halogen-based flame retardants and becoming the mainstream approach. Among them, red phosphorus, as a typical inorganic phosphorus-based flame retardant, features low addition amount, excellent flame retardant performance, and minimal dripping, making it widely used in the flame retardant modification of polyolefins and engineering plastics. Organic phosphonates, ammonium polyphosphates, and other phosphorus-nitrogen synergistic flame retardants also occupy an important position in the field of high-performance composite materials.

[0003] However, red phosphorus-based flame retardants, primarily based on red phosphorus, present significant technical challenges in practical applications. During storage, high-temperature processing, and long-term service, red phosphorus readily absorbs moisture and oxygen from the environment, undergoing oxidation and disproportionation, leading to yellowing and darkening of the product surface and affecting its appearance. More critically, red phosphorus decomposes upon heating, releasing highly toxic and strongly reducing phosphine gas. This gas can cause electrochemical corrosion of precision metal contacts such as copper and silver in electronic and electrical products, leading to poor contact or even failure. Furthermore, the high polarity of red phosphorus results in poor interfacial compatibility with non-polar or weakly polar polymer matrices such as polyamides and polyesters, leading to uneven dispersion and a tendency to migrate and precipitate onto the product surface. To address these issues, engineers have introduced microencapsulation technology into the flame retardant field. This isolates the core material from the external environment, forming core-shell structured composite flame-retardant particles, thus resolving these problems.

[0004] In the prior art, patent CN103724664A uses ultrafine red phosphorus as the core material and phenol-formaldehyde prepolymer as the shell layer. Under the catalysis of persulfate, a phenolic resin coating layer is formed on the surface of red phosphorus through in-situ polymerization, which significantly improves the ignition point of red phosphorus and reduces the moisture absorption rate and PH3 release. Another patent CN110452528B uses lipophilic phosphoric acid ester to impregnate red phosphorus powder with an average particle size greater than 1500 mesh, and then uses melamine-formaldehyde resin as the packaging material to form a microcapsule shell through in-situ polymerization. Finally, it is composite extruded with nylon 6 to obtain flame-retardant engineering plastics that can reach the UL94V-0 level.

[0005] Despite these limitations, existing microencapsulated phosphorus-based flame retardants still face several significant application challenges. These include limited shell material availability leading to insufficient density and weak interfacial bonding with engineering plastic matrices such as polyamides and polyesters. Furthermore, the coating layer may crack under high temperatures or shear stress during application, resulting in incomplete PH3 inhibition and posing a continued risk of corrosion to high-end electronic and electrical metal components. Subsequent precipitation phenomena are also not completely eliminated. Therefore, addressing these issues, developing a microencapsulated phosphorus-based flame retardant with a dense shell, excellent compatibility with the polymer matrix, stable coating layer, and significantly reduced precipitation is crucial for expanding its application in high-end electronic and electrical components. Summary of the Invention

[0006] To address the aforementioned issues, the applicant has provided the following technical solutions: A microencapsulated phosphorus-based flame retardant, by weight, comprises the following raw materials: 90-110 parts red phosphorus powder, 45-65 parts shell layer composition, 10-20 parts shell layer additives, 1-2 parts dispersant, 0.8-1.5 parts wetting agent, 0.5-1 part pH buffer, 0.6-1.2 parts initiator, 1-2 parts dispersion stabilizer, 0.2-0.4 parts defoamer, 8-14 parts composite functional agent, 0.3-0.5 parts antioxidant, and 800-1000 parts deionized water.

[0007] In a preferred embodiment, the D50 particle size of the red phosphorus powder is 1.5~3μm.

[0008] In a preferred embodiment, the D50 particle size of the red phosphorus powder is 1.5~2μm.

[0009] In a preferred embodiment, the free phosphorus content of the red phosphorus powder is ≤0.1wt%.

[0010] In a preferred embodiment, the shell material is a combination of melamine, cyanuric acid and paraformaldehyde.

[0011] In a preferred embodiment, the mass ratio of melamine, cyanuric acid and paraformaldehyde is (5~7):(2~4):(2~4).

[0012] In a preferred embodiment, the mass ratio of melamine, cyanuric acid and paraformaldehyde is (5~6):(2~3):(2~3).

[0013] In a preferred embodiment, the degree of polymerization of the paraformaldehyde is 8 to 10.

[0014] In a preferred embodiment, the shell additive is a combination of polyethylene glycol, tris(2-hydroxyethyl) isocyanurate and γ-glycidoxypropyltrimethoxysilane.

[0015] In a preferred embodiment, the mass ratio of polyethylene glycol, tris(2-hydroxyethyl) isocyanurate and γ-glycidoxypropyltrimethoxysilane is (4~6):(6~8):(3~5).

[0016] In a preferred embodiment, the mass ratio of polyethylene glycol, tris(2-hydroxyethyl) isocyanurate and γ-glycidoxypropyltrimethoxysilane is (5~5.8):(6.5~7.5):(3.5~4).

[0017] In a preferred embodiment, the polyethylene glycol is polyethylene glycol 400 or polyethylene glycol 800.

[0018] This application addresses the contradiction between insufficient shell density and easy breakage during processing by adding shell additives. Through the cross-linking reaction of a high content of active hydroxyl groups with the shell resin, a high-density rigid-flexible block copolymer network is formed. Furthermore, while providing a dense barrier, the flexible segments effectively dissipate external shear stress, thereby significantly avoiding the contradiction between easy breakage of the coating layer during high-temperature processing and the degradation of barrier performance during long-term use. This improves the shell density while ensuring its excellent stability and compatibility, providing a foundation for improving overall application performance.

[0019] In a preferred embodiment, the dispersant is sodium hexametaphosphate or sodium polyacrylate.

[0020] In a preferred embodiment, the dispersant is sodium hexametaphosphate.

[0021] In a preferred embodiment, the wetting agent is at least one selected from OP-10, Tween 80, and sodium dodecylbenzenesulfonate.

[0022] In a preferred embodiment, the wetting agent is OP-10.

[0023] In a preferred embodiment, the pH buffer is anhydrous sodium acetate.

[0024] In a preferred embodiment, the initiator is a persulfate-based initiator.

[0025] In a preferred embodiment, the persulfate initiator is preferably potassium persulfate or ammonium persulfate.

[0026] In a preferred embodiment, the persulfate initiator is preferably potassium persulfate.

[0027] In a preferred embodiment, the dispersant stabilizer is at least one selected from polyvinyl alcohol, hydroxyethyl cellulose, and povidone.

[0028] In a preferred embodiment, the dispersant stabilizer is polyvinyl alcohol or hydroxyethyl cellulose.

[0029] In a preferred embodiment, the dispersant stabilizer is polyvinyl alcohol 1788.

[0030] In a preferred embodiment, the defoamer is tributyl phosphate or polyoxypropylene glycerol ether.

[0031] In a preferred embodiment, the defoamer is tributyl phosphate.

[0032] In a preferred embodiment, the composite functional agent is a combination of pentaerythritol phosphate, N,N'-methylenebisacrylamide, and triallyl isocyanurate.

[0033] In a preferred embodiment, the mass ratio of pentaerythritol phosphate, N,N'-methylenebisacrylamide and triallyl isocyanurate is (6~8):(2~3):(1~2).

[0034] In a preferred embodiment, the mass ratio of pentaerythritol phosphate, N,N'-methylenebisacrylamide and triallyl isocyanurate is (7~7.5):(2~2.5):(1.3~1.6).

[0035] By adding composite functional agents, an anchoring network with a gradient crosslinking density is constructed in situ on the shell surface, and the interface is further compatibilized by hydrogen bonding. While promoting flame retardancy, the crosslinked anchoring layer is firmly bonded to the polymer molecular chain through chemical bonding and physical entanglement. Thus, on the basis of improving the interface compatibilization, the stability of ions is greatly enhanced, the migration and precipitation rate is reduced, and the anti-migration and stability are improved.

[0036] In a preferred embodiment, the antioxidant is at least one of antioxidant 168, antioxidant 1076, antioxidant 1098, and antioxidant BHT.

[0037] In a preferred embodiment, the antioxidant is antioxidant 168 and / or antioxidant 1076.

[0038] In a preferred embodiment, the antioxidant is antioxidant 168.

[0039] In a preferred embodiment, the mass ratio of the shell layer composite material, shell layer additive, and composite functional agent is (50~60):(12~18):(9~13).

[0040] In a preferred embodiment, the mass ratio of the shell composite material, shell additives and composite functional agents is (52~56):(14~17):(10~12).

[0041] A method for preparing the above-mentioned microcapsule-coated phosphorus-based flame retardant specifically includes the following steps: S1: Red phosphorus powder, dispersant, wetting agent, dispersion stabilizer and defoamer are added to 40-50 wt% of deionized water, dispersed at high speed to obtain a suspension, and then a pH buffer is added; S2: The suspension is transferred to a reaction vessel, the remaining deionized water is added, the temperature is raised and the shell layer material is added for heat preservation, then the shell layer additive and initiator are added, and the temperature is maintained again. After completion, the pH is adjusted with 10 wt% dilute acetic acid and the temperature is maintained again; S3: After completion, the temperature is lowered, the remaining raw materials are added in sequence, and the mixture is stirred at medium speed. After completion, the mixture is naturally cooled, filtered, washed with deionized water, and the filter cake is dried under vacuum to constant weight, pulverized and sieved to obtain the final product.

[0042] The preferred embodiment of the preparation method of the microencapsulated phosphorus-based flame retardant specifically includes the following steps: S1: Red phosphorus powder, dispersant, wetting agent, dispersion stabilizer, and defoamer are added to 40-50 wt% of deionized water, and dispersed at 800-1000 rpm for 45-60 min to obtain a suspension. A pH buffer is then added, and the pH is adjusted to 7.5-8; S2: The suspension is transferred to a reaction vessel, the remaining deionized water is added, and the temperature is raised to 70-75°C. The shell layer composition is added and kept at this temperature for 30-40 min. Then add the shell layer additive and initiator, keep warm for 1.5~2h, adjust the pH to 4.5~5.5 with 10wt% dilute acetic acid and continue to keep warm for 1.5~2h; S3: cool down to 65~70℃, add the remaining raw materials in sequence, keep warm and stir at 300~400rpm for 2~2.5h, cool naturally, filter, wash with 60~70℃ deionized water 4~6 times, dry the filter cake at 85~90℃ under vacuum of -0.09MPa for 4~5h to constant weight, pulverize and pass through a 300~400 mesh sieve to obtain the final product.

[0043] Application of the above-mentioned microencapsulated phosphorus flame retardant in engineering plastics and electronic and electrical component materials.

[0044] Beneficial effects of the application plan: 1. The microcapsule-coated phosphorus-based flame retardant prepared in this application effectively solves the problems of insufficient density and easy breakage during processing and shearing of traditional coating layers through a shell-structured raw material formulation. This allows the flame retardant to maintain the integrity of its coating during high-temperature processing and long-term service, significantly suppressing the risk of phosphine release and reducing the corrosion hazards to metal parts. On the other hand, it strengthens the interfacial bonding between the flame retardant and the polymer matrix, greatly improving the interfacial compatibility between the two, effectively preventing the migration and precipitation of the flame retardant during the use of the product, and ensuring the stability and durability of the long-term flame retardant performance and appearance of the material. It is especially suitable for applications in engineering plastics and electronic and electrical component materials where reliability and safety requirements are stringent.

[0045] 2. This application addresses the contradiction between insufficient shell density and easy breakage during processing by adding shell additives. Through the cross-linking reaction of a large amount of active hydroxyl groups with the shell resin, a high-density rigid-flexible block copolymer network is formed. The flexible segments effectively dissipate external shear stress, thereby significantly avoiding the contradiction between easy breakage of the coating layer during high-temperature processing and the degradation of barrier performance during long-term use. This improves the shell density while ensuring its excellent stability and compatibility.

[0046] 3. This application incorporates a composite functional agent to construct an anchoring network with a gradient cross-linking density in situ on the shell surface, and achieves further compatibilization of the interface through hydrogen bonding. While promoting flame retardancy, the cross-linked anchoring layer is firmly bonded to the polymer molecular chain through chemical bonding and physical entanglement. Thus, on the basis of improving the interface compatibilization, it significantly enhances the stability of ions, reduces the migration and precipitation rate, and improves the resistance to migration and precipitation and stability. Detailed Implementation

[0047] Example 1 A microencapsulated phosphorus-based flame retardant, by weight, comprises the following raw materials: 100 parts red phosphorus powder, 30 parts melamine, 12 parts cyanuric acid, 12 parts paraformaldehyde, 5.5 parts polyethylene glycol 400, 7 parts tris(2-hydroxyethyl) isocyanurate, 3.8 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 7.2 parts pentaerythritol phosphate, 2.3 parts N,N'-methylenebisacrylamide, 1.5 parts triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0048] The red phosphorus powder has a D50 particle size of 1.8 μm and a free phosphorus content of ≤0.1 wt%.

[0049] Paraformaldehyde has a degree of polymerization of 9. (Shandong Qiyun Chemical Co., Ltd.)

[0050] A method for preparing the above-mentioned microencapsulated phosphorus-based flame retardant specifically includes the following steps: S1: Add red phosphorus powder, sodium hexametaphosphate, OP-10, polyvinyl alcohol 1788 and tributyl phosphate to 40wt% of deionized water, disperse at 900rpm for 50min to obtain a suspension, then add anhydrous sodium acetate and adjust the pH to 7.8 with 10wt% dilute acetic acid.

[0051] S2: Transfer the suspension to the reactor, add the remaining deionized water, heat to 72°C, add melamine, cyanuric acid and paraformaldehyde and keep warm for 35 minutes, then add polyethylene glycol 400, tris(2-hydroxyethyl) isocyanurate, γ-glycidyl etheroxypropyltrimethoxysilane and potassium persulfate, keep warm for 1.5 hours, adjust the pH to 5.0 with 10wt% dilute acetic acid and continue to keep warm for 2 hours.

[0052] S3: Cool down to 68℃, add the remaining raw materials in sequence, keep warm and stir at 350rpm for 2h, after completion, cool naturally, filter, wash 5 times with 65℃ deionized water, dry the filter cake at 88℃ under vacuum at -0.09MPa for 4.5h to constant weight, pulverize and pass through a 350 mesh sieve to obtain the final product.

[0053] Example 2 A microencapsulated phosphorus-based flame retardant differs from Example 1 in that, by weight, its raw materials include: 100 parts red phosphorus powder, 30 parts melamine, 12 parts cyanuric acid, 12 parts paraformaldehyde, 5.5 parts polyethylene glycol 400, 7 parts tris(2-hydroxyethyl) isocyanurate, 3.8 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 8 parts pentaerythritol phosphate, 2 parts N,N'-methylenebisacrylamide, 2 parts triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0054] The remaining schemes and preparation methods are the same as in Example 1.

[0055] Example 3 A microencapsulated phosphorus-based flame retardant, by weight, comprises the following raw materials: 100 parts red phosphorus powder, 28 parts melamine, 14 parts cyanuric acid, 13 parts paraformaldehyde, 6 parts polyethylene glycol 400, 6 parts tris(2-hydroxyethyl) isocyanurate, 4.5 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 6 parts pentaerythritol phosphate, 3 parts N,N'-methylenebisacrylamide, 1 part triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0056] The D50 particle size of the red phosphorus powder is 2μm, and the free phosphorus content is ≤0.1wt%.

[0057] Paraformaldehyde has a degree of polymerization of 10. (Shandong Qiyun Chemical Co., Ltd.)

[0058] The remaining schemes and preparation methods are the same as in Example 1.

[0059] Comparative Example 1 A microencapsulated phosphorus-based flame retardant, different from Example 1: The microencapsulated phosphorus-based flame retardant, by weight, comprises the following raw materials: 100 parts red phosphorus powder, 35 parts melamine, 18 parts cyanuric acid, 15 parts paraformaldehyde, 3.5 parts polyethylene glycol 400, 3.5 parts tris(2-hydroxyethyl) isocyanurate, 2 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 4.5 parts pentaerythritol phosphate, 1.2 parts N,N'-methylenebisacrylamide, 0.5 parts triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0060] The remaining schemes and preparation methods are the same as in Example 1.

[0061] Comparative Example 2 A microencapsulated phosphorus-based flame retardant, differing from Example 1, comprises the following raw materials by weight: 100 parts red phosphorus powder, 30 parts melamine, 12 parts cyanuric acid, 12 parts paraformaldehyde, 1.2 parts polyethylene glycol 400, 9 parts tris(2-hydroxyethyl) isocyanurate, 4.5 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 8 parts pentaerythritol phosphate, 2 parts N,N'-methylenebisacrylamide, 2 parts triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0062] The remaining schemes and preparation methods are the same as in Example 1.

[0063] Comparative Example 3 A microencapsulated phosphorus-based flame retardant, differing from Example 1, comprises the following raw materials by weight: 100 parts red phosphorus powder, 30 parts melamine, 12 parts cyanuric acid, 12 parts paraformaldehyde, 5.5 parts polyethylene glycol 400, 7 parts tris(2-hydroxyethyl) isocyanurate, 3.8 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 10 parts pentaerythritol phosphate, 0.3 parts N,N'-methylenebisacrylamide, 3.5 parts triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0064] The remaining schemes and preparation methods are the same as in Example 1.

[0065] Comparative Example 4 A microencapsulated phosphorus-based flame retardant, differing from Example 1, comprises, by weight, the following raw materials: 100 parts red phosphorus powder, 30 parts melamine, 12 parts cyanuric acid, 12 parts paraformaldehyde, 5.5 parts polyethylene glycol 400, 7 parts tris(2-hydroxyethyl) isocyanurate, 3.8 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 4.5 parts pentaerythritol phosphate, 5 parts N,N'-methylenebisacrylamide, 0.2 parts triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0066] The remaining schemes and preparation methods are the same as in Example 1.

[0067] Comparative Example 5 A microencapsulated phosphorus-based flame retardant, differing from Example 1, comprises the following raw materials by weight: 100 parts red phosphorus powder, 40 parts melamine, 10 parts cyanuric acid, 5.5 parts paraformaldehyde, 5.5 parts polyethylene glycol 400, 7 parts tris(2-hydroxyethyl) isocyanurate, 3.8 parts γ-glycidyl etheroxypropyltrimethoxysilane, 1.5 parts sodium hexametaphosphate, 1 part OP-10, 0.8 parts anhydrous sodium acetate, 1 part potassium persulfate, 1.5 parts polyvinyl alcohol 1788, 0.3 parts tributyl phosphate, 8 parts pentaerythritol phosphate, 2 parts N,N'-methylenebisacrylamide, 2 parts triallyl isocyanurate, 0.4 parts antioxidant 168, and 900 parts deionized water.

[0068] The remaining schemes and preparation methods are the same as in Example 1.

[0069] Performance Evaluation 1. Phosphine (PH3) release: Weigh 10g of sample and place it in a 500mL sealed glass container. Heat at 120℃ for 24h. Use a PH3 gas detection tube to extract 100mL of gas from the container and read the PH3 concentration (ppm). Measure each sample 10 times and record the average value in Table 1.

[0070] 2. Thermogravimetric analysis: Weigh 10 mg of sample and place it in a thermogravimetric analyzer. Under a nitrogen atmosphere, raise the temperature from room temperature to 600 °C at a rate of 10 °C / min. Record the temperature at which the sample loses 5% of its weight. Take 10 measurements for each sample and record the average value in Table 1.

[0071] 3. Anti-exudation property: The flame retardant sample and polyamide 6 were melt-blended and extruded in a twin-screw extruder at a mass ratio of 25:75, and injection molded into a 50mm×50mm×2mm sample. The sample was placed in a 120℃ forced-air drying oven for 72h for aging. After taking it out, the area ratio of exudate on the sample surface was observed under a microscope. Five fields of view were randomly selected and the average value was recorded in Table 1.

[0072] 4. Interface compatibility: Flame-retardant PA6 specimens were prepared according to the above anti-exudation test method. Their tensile strength was tested according to GB / T 1040 standard, and the retention rate (%) was calculated based on the tensile strength of pure PA6. Tensile strength retention rate = sample tensile strength / tensile strength of pure PA6 × 100%. The average value of 10 specimens was recorded in Table 1.

[0073] Test Summary: The PH3 release amount of Examples 1-3 was 35-42 ppm, the thermogravimetric temperature was 305-318℃, the surface precipitation area ratio was 0.9-1.5%, and the tensile strength retention rate was 95.2-97.5%. The performance of Comparative Examples 1-5 was significantly inferior to that of the Examples, with Comparative Example 1 showing a PH3 release amount as high as 178 ppm and Comparative Example 4 showing a surface precipitation area ratio as high as 7.1%. This indicates that the technical solution of this application significantly improves the density, thermal stability, interfacial compatibility, and anti-precipitation performance of the coating layer.

[0074] Table 1 Performance Evaluation Table

[0075] Examples 1-3 all showed significantly better performance than the comparative examples, verifying the effectiveness of the technical solution presented in this application. The synergistic effect of the rigid crosslinking of THEIC and the flexible toughening of PEG in the shell layer additives gives the coating layer both high density and shear toughness, effectively suppressing PH3 release and preventing processing cracking. The appropriate ratio of raw materials in the composite functional agent, through the combined effect of interfacial hydrogen bonding compatibilization and multi-point chemical anchoring, significantly increases the stability and strength between the flame retardant and the matrix, achieving excellent comprehensive performance including low PH3 release, high resistance to precipitation, and superior mechanical properties.

[0076] Comparative Examples 1 and 2 suffered from an imbalance in the proportion of shell raw materials, resulting in insufficient shell density or increased brittleness, and their PH3 release and thermal weight loss temperatures were significantly worse than those of the Examples. Comparative Examples 3 and 4 suffered from changes in the proportion of composite functional agent raw materials, resulting in incomplete interfacial compatibilization or anchoring network and severe surface precipitation. Comparative Example 5 suffered from incomplete shell condensation reaction and defects in the coating layer structure, which resulted in the comparative examples achieving significantly worse overall performance than the Examples.

Claims

1. A microencapsulated phosphorus-based flame retardant, characterized in that: The raw material formula, by weight, includes: 90-110 parts red phosphorus powder, 45-65 parts shell layer composition, 10-20 parts shell layer additive, 1-2 parts dispersant, 0.8-1.5 parts wetting agent, 0.5-1 part pH buffer, 0.6-1.2 parts initiator, 1-2 parts dispersion stabilizer, 0.2-0.4 parts defoamer, 8-14 parts composite functional agent, 0.3-0.5 parts antioxidant, and 800-1000 parts deionized water; The shell material is a combination of melamine, cyanuric acid and paraformaldehyde, with a mass ratio of (5~7):(2~4):(2~4). The degree of polymerization of the paraformaldehyde is 8 to 10; The shell additive is a combination of polyethylene glycol, tris(2-hydroxyethyl) isocyanurate and γ-glycidoxypropyltrimethoxysilane.

2. The microencapsulated phosphorus-based flame retardant according to claim 1, characterized in that: The D50 particle size of the red phosphorus powder is 1.5~3μm.

3. The microencapsulated phosphorus-based flame retardant according to claim 2, characterized in that: The mass ratio of polyethylene glycol 400, tris(2-hydroxyethyl) isocyanurate and γ-glycidoxypropyltrimethoxysilane is (4~6):(6~8):(3~5).

4. The microencapsulated phosphorus-based flame retardant according to claim 3, characterized in that: The polyethylene glycol is polyethylene glycol 400 or polyethylene glycol 800.

5. The microencapsulated phosphorus-based flame retardant according to claim 4, characterized in that: The dispersant is sodium hexametaphosphate or sodium polyacrylate.

6. The microencapsulated phosphorus-based flame retardant according to claim 5, characterized in that: The initiator is a persulfate initiator.

7. The microencapsulated phosphorus-based flame retardant according to claim 6, characterized in that: The mass ratio of the shell composition material, shell additives and composite functional agents is (50~60):(12~18):(9~13).

8. The microencapsulated phosphorus-based flame retardant according to claim 7, characterized in that: The composite functional agent is a combination of pentaerythritol phosphate, N,N'-methylenebisacrylamide and triallyl isocyanurate, in a mass ratio of (6~8):(2~3):(1~2).

9. A method for preparing a microencapsulated phosphorus-based flame retardant according to any one of claims 1 to 8, characterized in that: Specifically, the following steps are included: S1: Add red phosphorus powder, dispersant, wetting agent, dispersion stabilizer and defoamer to 40~50wt% of deionized water, disperse at high speed to obtain a suspension, and then add pH buffer. S2: Transfer the suspension to the reactor, add the remaining deionized water, heat up, add the shell layer material and keep it warm, then add the shell layer additive and initiator, continue to keep it warm, and after completion, adjust the pH with 10wt% dilute acetic acid and keep it warm again; S3: After completion, cool down, add the remaining raw materials in sequence, keep it warm and stir at medium speed, after completion, cool naturally, filter, wash with deionized water, dry the filter cake under vacuum to constant weight, crush and sieve to obtain the final product.

10. The application of a microencapsulated phosphorus flame retardant according to any one of claims 1 to 8 in engineering plastics and electronic and electrical component materials.

Citation Information

Patent Citations

  • Novel fire retardant microencapsulated red phosphorus and preparation method thereof

    CN103724664A